2017
DOI: 10.1186/s13024-017-0163-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal progression of ubiquitin-proteasome system inhibition after status epilepticus suggests protective adaptation against hippocampal injury

Abstract: BackgroundThe ubiquitin-proteasome-system (UPS) is the major intracellular pathway leading to the degradation of unwanted and/or misfolded soluble proteins. This includes proteins regulating cellular survival, synaptic plasticity and neurotransmitter signaling; processes controlling excitability thresholds that are altered by epileptogenic insults. Dysfunction of the UPS has been reported to occur in a brain region- and cell-specific manner and contribute to disease progression in acute and chronic brain disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…To explore the response of GSK-3β to prolonged seizures, we used a well-characterized model of intra-amygdala KA-induced SE in mice 59 . As previously reported, SE resulted in hippocampal damage that was mainly localized to the ipsilateral CA3 subfield, although scattered cell death was present in the CA1 and the hilus regions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the response of GSK-3β to prolonged seizures, we used a well-characterized model of intra-amygdala KA-induced SE in mice 59 . As previously reported, SE resulted in hippocampal damage that was mainly localized to the ipsilateral CA3 subfield, although scattered cell death was present in the CA1 and the hilus regions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that experimental status epilepticus leads to an inhibition of the ubiquitin‐proteasome system (UPS), thereby potentially increasing P2Y 1 levels. UPS function is also altered during chronic epilepsy in mice . Seizure‐induced changes in receptor stability or internalization may also account for the increase in P2Y 1 levels .…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction and qPCR. RNA extraction was performed using the Trizol method, as described previously (Engel et al, 2017b). Quantity and quality of RNA were measured using a Nanodrop Spectrophotometer (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis. Western blot analysis was performed as described previously (Engel et al, 2017b). Lysis buffer containing phosphatase and protease inhibitors was used to homogenize hippocampal tissue and extract protein, which was quantified using a Tecan plate reader at 560 nm; 30 g of protein samples was loaded onto an acrylamide gel and separated by SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%